Global and regional abatement costs of Nationally Determined Contributions (NDCs) and of enhanced action to levels well below 2 °C and 1.5 °C. Issue 71 (May 2017) - Hof, Andries F.; den Elzen, Michel G.J.; Admiraal, Annemiek; Roelfsema, Mark; Gernaat, David E.H.J.; van Vuuren, Detlef P.
Highlights: Annual abatement costs of achieving national climate plans (NDCs) are projected. The costs are very sensitive to different socio-economic assumptions. The costs of the conditional NDCs are projected at USD 97–191 billion by 2030. There are large differences in costs of achieving NDCs between countries. The costs of achieving 2 °C are 3–3.5 times the costs of achieving conditional NDCs. Abstract: As part of the Paris climate agreement, countries have submitted (Intended) Nationally Determined Contributions (NDCs), which includes greenhouse gas reduction proposals beyond 2020. In this paper, we apply the IMAGE integrated assessment model to estimate the annual abatement costs of achieving the NDC reduction targets, and the additional costs if countries would take targets in line with keeping global warming well below 2 °C and "pursue efforts" towards 1.5 °C. We have found that abatement costs are very sensitive to socio-economic assumptions: under Shared Socioeconomic Pathway 3 (SSP3) assumptions of slow economic growth, rapidly growing population, and high inequality, global abatement costs of achieving the unconditional NDCs are estimated at USD135 billion by 2030, which is more than twice the level as under the more sustainable socio-economic assumptions of SSP1. Furthermore, we project that the additional costs of full implementation of the conditional NDCs are substantial, ranging from 40 to 55 billion USD, depending on socio-economic assumptions. Of the ten major emitting economies, Brazil, Canada and the USA are projected to have the highest cots as share of GDP to implement the conditional NDCs, while the costs for Japan, China, Russia, and India are relatively low. Allowing for emission trading could decrease global costs substantially, by more than half for the unconditional NDCs and almost by half for the conditional NDCs. Finally, the required effort in terms of abatement costs of achieving 2030 emission levels consistent with 2 °C pathways would be at least three times higher than the costs of achieving the conditional NDCs – even though reductions need to be twice as much. For 1.5 °C, the costs would be 5–6 times as high.